Beyond interviewer demeanour and post-event misinformation: the influence of temperament and parenting styles on children’s eyewitness reports - Wong, Yi Shan; Pye, Rachel; Su, I. An; Ceci, Stephen J.; Hamsan, Hanina; Kamaluddin, Mohammad Rahim; Ahmad Badayai, Abdul Rahman; Chung, Kai Li (Routledge, 2025)
Children often serve as key witnesses in child abuse investigations. However, prior research has shown that children’s testimony may be inaccurate due to susceptibility to false memories and suggestibility. Existing studies have often assessed interviewing contexts with little consideration of the child’s cultural context and reciprocal behaviour, potentially overlooking how individuals vary in their responses to different interview conditions. To explore the factors and conditions under which children can accurately report information and their vulnerability to suggestions, this study incorporated both situational and dispositional factors to explore the relative contributions of interviewing conditions (i.e. interviewer demeanour and exposure to misinformation) and individual differences variables (i.e. intelligence, temperament, trait and state anxiety, and parenting styles) on children’s recall and suggestibility. One-hundred and sixty Malaysian children aged between 7 and 10 years (M = 8.26; SD = 0.75) were assessed using a video suggestibility paradigm. Multiple regression analyses revealed that non-supportive interviewer demeanour and non-exposure to misinformation predicted improved recall. Intelligence and temperament emerged as significant predictors of accurate recall. Notably, findings shed light on the role of authoritarian parenting on suggestibility. Future research is needed to enhance our understanding of how cultural factors and the environment influence children’s eyewitness reports.